2022
DOI: 10.1186/s13063-021-05969-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of transcutaneous electrical stimulation to non-pharmacological measures in labor pain: study protocol for a randomized controlled trial

Abstract: Background Labor, although natural and physiological, is a period that can be marked by stress, pain, anxiety, suffering, fear, and anguish for a woman. Thus, non-pharmacological methods that reduce pain during labor are important to allow a better experience without the use of medications. Therefore, the aim of this study is to evaluate the effects of non-pharmacological pain relief methods, added or not to the application of transcutaneous electrical stimulation (TENS), on pain, satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In contrast, various nonpharmacological therapies seem to be safe to minimize pain intensity, increase maternal satisfaction, as well as delay pharmacological analgesics 13,31 . Nonpharmacological approaches of pain relief may be utilized alone or with the multidisciplinary team (e.g., doctors, nursing technicians, and doulas), which depends on the choice of parturient women and the hospital's infrastructure 16 . In our study, the LeBeiEr delivery analgesia instrument was used for nonpharmacological approaches of pain relief in pregnant women, with the findings revealed that the nonpharmaceutical analgesia showed shorten labor duration and less postpartum bleeding volume.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, various nonpharmacological therapies seem to be safe to minimize pain intensity, increase maternal satisfaction, as well as delay pharmacological analgesics 13,31 . Nonpharmacological approaches of pain relief may be utilized alone or with the multidisciplinary team (e.g., doctors, nursing technicians, and doulas), which depends on the choice of parturient women and the hospital's infrastructure 16 . In our study, the LeBeiEr delivery analgesia instrument was used for nonpharmacological approaches of pain relief in pregnant women, with the findings revealed that the nonpharmaceutical analgesia showed shorten labor duration and less postpartum bleeding volume.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TENS provides electrical stimulation through the skin, through sensory stimuli that will carry information to the brain through afferent fibers to the dorsal horn of the Aß medulla. Therefore, there is a blockage of pain impulses to the brain, as this fiber transmits the information faster than the fibers responsible for transmitting the pain through (the gate control theory) [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Studies have explored the effects of various strategies, such as epidurals and opioids to reduce labor pain while considering women experiences and views. [11,12] Although empirical evidence indicates that different medical interventions can alleviate the pain that women experience during childbirth, the outcomes have been inconclusive. While some researchers have found that nonpharmacological pain relief techniques can empower women and that natural remedies may not be as effective as anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have explored the effects of various strategies, such as epidurals and opioids to reduce labor pain while considering women experiences and views. [ 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%